The meta-projects of the new community health centers, community hospitals and local operative centers for the Italian country: The meta-projects of the new CHCs, CHs and LOCs - Capolongo, Stefano; Buffoli, Maddalena; Gola, Marco; Borghini, Alice; Riano, Federica; Arruzzoli, Stefano; Brusamolin, Erica; Yu, Yong; Izzi, Alessandro; Mantoan, Domenico (Acta Biomedica Atenei Parmensis, 2023)
Background and aim. COVID-19 highlighted significant criticalities of the Italian National Healthcare System (NHS) and recently the Italian Government approved the National Recovery and Resilience Plan (NRRP) to relaunch its economy and at the same time to promote health, sustainability and digital innovation. Specifically, M6C1 (Mission 6 Component 1) wants to introduce Community Health Centers (CHCs), Community Hospitals (CHs) and Local Operative Centers (LOCs) to strength territorial healthcare services. Starting from the Italian Ministerial Decree n. 77 (2022), AGENAS (National Agency for Regional Healthcare System) and POLIMI (Politecnico di Milano) working group developed the meta-design guidelines for CHCs, CHs and LOCs facilities with the aim of supporting decision-makers to define spatial features and building performances in order to be responsive to functional issues.Methods. The spatial strategies of these facilities have been elicited through three different steps: a) a survey about the current national and international scenario regarding the territorial healthcare; b) a review of all national and regional regulations; c) the development of the meta-design guidelines have been elaborated from the analysis of the a) and b) steps.Results. The regulatory instructions and scientific indications collected through the literature have been translated into spatial and functional layouts. The services have been organized by homogeneous macro-areas and defined in a synoptic framework which shows the performance approach and their features. Each macro-area, sorted by type of functions, has been subdivided into a list of all its specific spatial units.Conclusions. The study conducted aims at supporting the planning of these facilities in relation to the catchment area and their sizing. It will be necessary to define the location by evaluating the possibility of setting them up within existing hospitals, as well as to guarantee a sustainable approach in the realization of these infrastructures.